Bank Health Ratio and Profitability of Commercial Banks in Indonesia: Optimal Strategies in Banking Intermediation Functions - Daulay, Ahmad Harun; Prasetyo, Alvin Sugeng (IPB University, 2025)
The objective of this study is to examine and analyze the impact of commercial bank health on the profitability of commercial banks in Indonesia. The analysis in this study employs panel data regression techniques with a time series spanning from 2010 to 2023 and a cross-section of 105 commercial banks in Indonesia. The study's findings indicate that most bank health indicators have a positive and significant impact on profitability. Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income Ratio (BOPO) are all significant determinants of bank profitability. Future policies should prioritize dynamic capital requirements, advanced risk management systems, liquidity monitoring, and operational digitalization to enhance the resilience and competitiveness of banks in Indonesia.